FERTILITY AND PREGNANCY DURING THE PANDEMIC AT THE DAYAK MERATUS TRIBE - Kartika, Norma Yuni; Farid, Fuad Muhajirin; Azizah, Nor Aufa (Universitas Airlangga, 2024)
Fertility rate in South Kalimantan in 2017 is the same as Indonesia’s in 2.4. This figure is below the target figure for the 2020-2021 National Medium-Term Development Plan (Rencana Pembangunan Jangka Menengah Nasional/RPJMN) in 2.1. This study aims to determine the factors affecting fertility and pregnancy which occurred during the pandemic in women of childbearing age (Wanita Usia Subur/WUS) of the Dayak Pitap tribe living in the Meratus Mountains, Ajung Village, Tebing Tinggi District, Balangan Regency, South Kalimantan Province. This study uses a quantitative approach with a survey method. The research sample taken was 70 respondents using the quota sampling method with the simple random sampling method. Data processing and analysis was carried out in three stages, to be specific univariate analysis, bivariate with Chi-square statistical test, and multivariate analysis using binary logistic regression model. The results of the analysis show that women of childbearing age from the Dayak Meratus/Dayak Pitap tribe who are under 35 years old and have finished elementary school are 24.4% more likely to have 2 children. Therefore, it could be concluded that age and level of education affect the fertility.